Predicting satisfaction with outcome and follow‐up care 5 years after bariatric surgery: A prospective evaluation - Ingela Lundin Kvalem; Louise Gabrielsen; Inger Eribe; Jon A. Kristinsson; Tom Mala (Wiley, 2022)
Abstract Objective Patient satisfaction is viewed as essential for a successful outcome of bariatric surgery. Few studies have explored long‐term satisfaction prospectively. This study aimed to examine pre‐ and post‐surgery predictors for satisfaction with follow‐up care, and change in outcome satisfaction from one to 5 years after bariatric surgery. Methods A sample of 210 participants was recruited from a single treatment center. Self‐reported and medical record data regarding mental and somatic health, body image, follow‐up attendance, and weight loss were obtained before, 1 year, and 5 years after surgery. Results Over 90% of the participants were satisfied with the results and treatment 1 year after surgery, while 69% had their outcome expectations fulfilled and 62% were satisfied with the follow‐up 5 years after surgery. A shift from initial satisfaction to unfulfillment of expectations was predicted by baseline body dissatisfaction, greater percentage of weight regain after initial weight loss, and more discomfort from somatic symptoms 5 years after surgery. In addition to symptom discomfort, worry about surgery predicted satisfaction with follow‐up care. Conclusion At 5 years, one‐fifth of those initially satisfied reported that bariatric surgery had failed to meet their expectations. This suggests that outcome expectations related to weight loss, somatic symptoms, and body image need to be addressed both before and after bariatric surgery.